Association between inflammation and left ventricular thrombus formation following ST-elevation myocardial infarction. (15th August 2022) - Lechner, Ivan; Reindl, Martin; Tiller, Christina; Holzknecht, Magdalena; Fink, Priscilla; Plangger, Johannes; Mayr, Agnes; Klug, Gert; Bauer, Axel; Reinstadler, Sebastian J.; Metzler, Bernhard
Abstract: Background: Current evidence suggests a link between the inflammatory state and left ventricular (LV) thrombus formation following ST-elevation myocardial infarction (STEMI). However, a comprehensive study investigating the association between inflammatory biomarkers and LV thrombus diagnosed by cardiac magnetic resonance (CMR) is lacking. Methods: We studied 309 patients with acute STEMI treated with primary percutaneous coronary intervention (pPCI) from the prospective MARINA-STEMI cohort study. Concentrations of high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), white blood cell count (WBCc), fibrinogen and D-dimer were measured two days after STEMI. Infarct characteristics and presence of LV thrombi were assessed with the use of contrast-enhanced CMR at a median of 4 (interquartile range [IQR] 3–5) days after pPCI. Results: In total, 309 STEMI patients (18% female) with a median age of 57 (IQR 52–65) years were included. A LV thrombus was observed in 8% ( n = 24) of the overall cohort and in 15% of patients with an anterior STEMI. Hs-CRP (OR 2.16, 95% CI 1.54–3.02, p < 0.001), IL-6 (OR 2.38, 95% CI 1.48–3.81, p < 0.001) and fibrinogen levels (OR 2.05, 95% CI 1.40–3.00, p < 0.001) were significantly associated with presence of LV thrombus. Among all assessed inflammatory biomarkers, only hs-CRP was independently associated with LV thrombus after adjustment for markers of inflammation and CMR parameters (OR 1.77, 95% CI 1.21–2.59, p = 0.004). Conclusion: In patients with STEMI treated with pPCI, inflammatory markers (hs-CRP, IL-6 and fibrinogen) are associated with the presence of LV thrombus. However, only hs-CRP was independently associated with the occurrence of LV thrombi, highlighting the key role of CRP as clinical risk marker for LV thrombus formation in STEMI patients treated with pPCI. Highlights: Inflammatory markers are strongly associated with the presence of LVT in STEMI patients. Among several inflammatory biomarkers and CMR parameters, only hs-CRP was independently associated with the occurrence of LVT. This highlights the key role of CRP as clinical risk marker for LV thrombus formation in STEMI.